Preface - Peter Hinow; Pierre Magal; Shigui Ruan (Mathematical Biosciences and Engineering)
This special issue is dedicated to the 70th birthday of Glenn F. Webb.The topics of the 12 articles appearing in this special issue includeevolutionary dynamics of population growth, spatio-temporal dynamicsin reaction-diffusion biological models, transmission dynamics ofinfectious diseases, modeling of antibiotic-resistant bacteria in hospitals,analysis of Prion models, age-structured models in ecology and epidemiology,modeling of immune response to infections, modeling of cancer growth, etc.These topics partially represent the broad areas of Glenn's research interest.For more information please click the “Full Text” above.